Applying socially responsible entrepreneurship in tourism businesses - Botlíková Milena; Botlík Josef; Stuchlíková Jana (SHS Web of Conferences, 2020)
The current global world is recording and progressively developing tourism industry by the expansion of hotels and catering facilities. The development of tourism is inextricably linked with positive impacts such as growth of employment, increase in business activities, etc. On the other hand, the connection between tourism and global problems has been actively discussed in recent years. With the development of tourism occurs to the congestion of destinations, globalization brings degeneration of national cultures, grow gas emissions, soil erosion and increased waste production. The research revealed that Czech citizens consider the accumulation of waste as one of the global problems right after the lack of drinking water. One possibility of effective management of corporate waste is the implementation of waste management strategy in the management of the company. Businesses should aim to reduce, sort and recycle. The aim of the article was to compare the development of waste production in the European Union and the Czech Republic in connection with tourism and to evaluate the approach of Czech hotel companies to the issue of waste management. On the basis of the analysis, it can be stated that the amount of waste is gradually increasing and the hotels have some reserves.